Czech Arts Therapies in Educational Institutions - Jiří Kantor; Miroslav Chráska; Libuše Ludíková (MDPI AG, 2019)
The purpose of this paper was to better understand the current practice of arts therapy in educational institutions in the Czech Republic comparing it to that in health-care institutions and other working environments. The research goal was to analyze the prevalence of the different fields of arts therapy, the main difficulties of clients, the therapeutic forms, the ways of interdisciplinary cooperation, and the groups of therapists (according to their age and duration of practice). The data collected from the first national survey using “The Practice of Arts Therapies„ questionnaire were analyzed with descriptive and inductive statistics (Chi-square test). The 142 respondents who participated in the study were contacted mainly through professional associations. The significant characteristics of arts therapies in educational environments are linked to the diffusion of the respective arts therapy fields (music therapy being the most prevalent), the main difficulties of pupils (learning difficulties/multiple disabilities or no obvious problems), and to the length of practice of the respondents. The results can be used for the creation of a research-based map of Czech arts therapies in educational institutions and for further development of this area.